2016
DOI: 10.3758/s13423-016-1146-y
|View full text |Cite
|
Sign up to set email alerts
|

Voice-based assessments of trustworthiness, competence, and warmth in blind and sighted adults

Abstract: The study of voice perception in congenitally blind individuals allows researchers rare insight into how a lifetime of visual deprivation affects the development of voice perception. Previous studies have suggested that blind adults outperform their sighted counterparts in low-level auditory tasks testing spatial localization and pitch discrimination, as well as in verbal speech processing; however, blind persons generally show no advantage in nonverbal voice recognition or discrimination tasks. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 52 publications
(63 reference statements)
8
44
0
1
Order By: Relevance
“…Nearly all prior work has manipulated pitch by ±0.5 ERBs (Klofstad et al ., ; O'Connor & Barclay, ; Vukovic et al ., ), with the exception of a ±0.75 ERB manipulation by Oleszkiewicz et al . (). Differences among study findings are also unlikely to be driven by speech content.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Nearly all prior work has manipulated pitch by ±0.5 ERBs (Klofstad et al ., ; O'Connor & Barclay, ; Vukovic et al ., ), with the exception of a ±0.75 ERB manipulation by Oleszkiewicz et al . (). Differences among study findings are also unlikely to be driven by speech content.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with prior work finding that lower‐pitched male voices are perceived as more attractive but as less trustworthy than are higher‐pitched male voices (Montano et al ., ; O'Connor & Barclay, ; O'Connor & Feinberg, ; O'Connor et al ., ; O'Connor, Pisanski, et al ., ). Some other research has either failed to detect a main effect of voice pitch on trustworthiness (Klofstad et al ., ; Vukovic et al ., ) or has found that lower‐pitched male voices are perceived as relatively trustworthy (Oleszkiewicz et al ., ; Tigue et al ., ). The reason for this disagreement among findings is currently unclear, but is unlikely to be driven by the magnitude of pitch manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several acoustic features influence the perception of how trustworthy and cooperative the speaker is (Belin et al, 2017;Knowles & Little, 2016;Montano et al, 2017;O'Connor & Barclay, 2017;Oleszkiewicz et al, 2017;Ponsot et al, 2018;Tigue et al, 2012;Tsantani et al, 2016). Their influence could stem from the pleiotropic effect of testosterone on both acoustic features and cooperative behaviours (O'Connor & Barclay, 2017).…”
Section: Discussionmentioning
confidence: 99%